Potential Character Development of Students in Karuna Jala Tangerang Banten Sunday School - I Ketut Damana (International Journal of Educational Management and Innovation, 2022)
Objectives The potential for character development in Sunday school is motivated by changes in student behavior. The study tries to examine the results of the potential development of students' character. This study uses a qualitative method with a pragmatic approach. The data collection of this study wasdone through documentation and interviews with Miles andHuberman models. This study showed that, Appreciating theteacher's attitude toward the potential of character building of Buddhist Sunday school in Karuna Jala in Tangerang Banten. Supporting factors in applying the potential of character building. Challenges of the potential character building of Buddhist Sunday school. They were organizing the potential formation of the character of Buddhist Sunday school in Tangerang Jala sack monastery. Therefore, learners andteachers should be able to use the character's potential.